Progerin accelerates atherosclerosis by inducing endoplasmic reticulum stress in vascular smooth muscle cells - Magda R Hamczyk; Ricardo Villa‐Bellosta; Víctor Quesada; Pilar Gonzalo; Sandra Vidak; Rosa M Nevado; María J Andrés‐Manzano; Tom Misteli; Carlos López‐Otín; Vicente Andrés (EMBO Molecular Medicine)
Abstract Hutchinson–Gilford progeria syndrome (HGPS) is a rare genetic disorder caused by progerin, a mutant lamin A variant. HGPS patients display accelerated aging and die prematurely, typically from atherosclerosis complications. Recently, we demonstrated that progerin‐driven vascular smooth muscle cell (VSMC) loss accelerates atherosclerosis leading to premature death in apolipoprotein E‐deficient mice. However, the molecular mechanism underlying this process remains unknown. Using a transcriptomic approach, we identify here endoplasmic reticulum stress (ER) and the unfolded protein responses as drivers of VSMC death in two mouse models of HGPS exhibiting ubiquitous and VSMC‐specific progerin expression. This stress pathway was also activated in HGPS patient‐derived cells. Targeting ER stress response with a chemical chaperone delayed medial VSMC loss and inhibited atherosclerosis in both progeria models, and extended lifespan in the VSMC‐specific model. Our results identify a mechanism underlying cardiovascular disease in HGPS that could be targeted in patients. Moreover, these findings may help to understand other vascular diseases associated with VSMC death, and provide insight into aging‐dependent vascular damage related to accumulation of unprocessed toxic forms of lamin A.